2002
DOI: 10.7326/0003-4819-137-7-200210010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Statin-Associated Myopathy with Normal Creatine Kinase Levels

Abstract: Some patients who develop muscle symptoms while receiving statin therapy have demonstrable weakness and histopathologic findings of myopathy despite normal serum creatine kinase levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
289
1
17

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(332 citation statements)
references
References 17 publications
17
289
1
17
Order By: Relevance
“…Interestingly, muscle biopsies showed evidence of mitochondrial dysfunction, including increased lipid stores, fibres that did not stain for cytochrome oxidase activity and ragged red fibres. These pathological and biochemical findings in patients with statin myotoxicity suggest impaired fatty acid oxidation (14). These findings reversed when the patients were no longer receiving statin therapy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Interestingly, muscle biopsies showed evidence of mitochondrial dysfunction, including increased lipid stores, fibres that did not stain for cytochrome oxidase activity and ragged red fibres. These pathological and biochemical findings in patients with statin myotoxicity suggest impaired fatty acid oxidation (14). These findings reversed when the patients were no longer receiving statin therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Phillips et al (14) reported patients who developed muscle symptoms but had a normal CK concentration while receiving statin therapy. These patients had demonstrable weakness measured by standard techniques of functional capacity and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, a leading lipidologist expressed an opinion that about 5% of people taking lovastatin developed some kind of myopathy 'with or without elevation of muscle enzyme levels' [3]. In 2002, Phillips et al described biopsy-proven myopathy accompanied by weakness in statin-treated patients without elevations of serum creatine kinase (CK) [4]. Lovastatin has been shown to potentiate post-exercise CK elevation, and clinical experience has suggested interaction between statins and exercise in muscle adverse effects [5,6].…”
mentioning
confidence: 99%
“…Historically, the primary goal of managing Type 2 diabetes has been the control of blood glucose levels; however, more recently, the importance of cardiovascular risk has been emphasized (The United Kingdom Prospective Diabetes Study (UKPDS) Group 1998. (Phillips et al, 2002, Pasternak et al, 2002. However, none of the published guidelines explicitly consider the trade-off between the benefits of reduction in CHD and stroke risks and the adverse side effects of treatment.…”
Section: Introductionmentioning
confidence: 99%